2014
DOI: 10.1590/1519-6984.20612
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Planktonic Shrimp Lucifer (Thompson, 1829) (Decapoda, Sergestoidea) off the Amazon

Abstract: Lucifer faxoni (BORRADAILE, 1915) and L. typus (EDWARDS, 1837) are species first identified in the neritic and oceanic waters off the Amazon. Samplings were made aboard the vessel "Antares" at 22 stations in July and August, 2001 with a bongo net (500-μm mesh size). Hydrological data were taken simultaneously for comparative purposes. L. faxoni was present at thirteen of the fourteen neritic stations analysed, as well as at five of the eight oceanic stations. L. typus was present at three of the fourteen ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Their diet consists mainly of copepods, exerting a considerable influence on the structure of lower trophic levels ( Pearre, 1980 ). Additionally, the holoplanktonic decapod Belzebub faxoni (cited as Lucifer faxoni ) was found to be common in studies conducted in coastal areas of the Amazon ( Melo N.F.A.C. et al, 2014 ; Conroy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their diet consists mainly of copepods, exerting a considerable influence on the structure of lower trophic levels ( Pearre, 1980 ). Additionally, the holoplanktonic decapod Belzebub faxoni (cited as Lucifer faxoni ) was found to be common in studies conducted in coastal areas of the Amazon ( Melo N.F.A.C. et al, 2014 ; Conroy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The available zooplankton data for the Amazon coast are very limited because this is one of the areas in the Atlantic equatorial region with little available information ( Boltovskoy, 1999 ; Conroy et al, 2016 ). The relevant reported zooplankton studies include those of Dahl (1894) and Björnberg (1963) on copepods; Vannucci and Queiroz (1963) and Jacob et al (1966) on zooplankton biovolume; Paranaguá (1966) on general zooplankton taxa; Calef and Grice (1967) , related to the total zooplankton volume and copepod abundance, in addition to cladoceran and decapod abundances associated with the low-salinity plume; Alvariño (1969) on chaetognaths; Montú (1994) on amphipods; Melo N.F.A.C. et al (2014) on the distribution of Luciferidae; and Conroy et al (2016) on meso- and microzooplankton grazing in the Amazon River plume.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a previous study on holoplanktonic luciferid shrimps (Melo et al, 2014) showed that their abundance decreased substantially along a gradient from the coast towards offshore waters, on the North Brazilian Shelf. Other studies of decapods in the study area were conducted by Cavalcante et al (2012), de Oliveira et al (2012), Carvalho et al (2013) and Nóbrega et al (2014).…”
Section: Introductionmentioning
confidence: 94%
“…In these environments, the exportation of meroplanktonic decapod larvae from mangroves to the open shelf is significant, since these habitats act as nurseries for several brachyuran and anomuran crabs species, penaeidean and caridean shrimps, and axiidean and gebiidean mud shrimps (Schwamborn et al, 1999;Kathiresan and Bingham, 2001). However, previous studies on the north Brazilian shelf influenced by the ARP and NBC retroflection indicated a low abundance of decapod larvae and a dominance of holoplanktonic decapods, mainly represented by holoplanktonic shrimps of the families Luciferidae and Sergestidae (Melo et al, 2014;Conroy et al, 2016;Neumann-Leitão et al, 2018). A dominance of holoplanktonic decapod shrimps is usually reported from oceanic areas without any estuarine influence (Judkins, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation